2016
DOI: 10.1121/1.4943627
|View full text |Cite
|
Sign up to set email alerts
|

Software for real-time localization of baleen whale calls using directional sonobuoys: A case study on Antarctic blue whales

Abstract: Directional frequency analysis and recording (DIFAR) sonobuoys can allow real-time acoustic localization of baleen whales for underwater tracking and remote sensing, but limited availability of hardware and software has prevented wider usage. These software limitations were addressed by developing a module in the open-source software PAMGuard. A case study is presented demonstrating that this software provides greater efficiency and accessibility than previous methods for detecting, localizing, and tracking An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Call recognition and pre‐processing was done using pamguard (version 1.11.00 BETA; Miller et al . ; http://www.pamguard.org), which also allowed us to check recognitions. Arthroleptella lightfooti calls consist of three pulses that make up a single note and are identified as a single frog call using a click detector in pamguard (see Stevenson et al .…”
Section: Methodsmentioning
confidence: 99%
“…Call recognition and pre‐processing was done using pamguard (version 1.11.00 BETA; Miller et al . ; http://www.pamguard.org), which also allowed us to check recognitions. Arthroleptella lightfooti calls consist of three pulses that make up a single note and are identified as a single frog call using a click detector in pamguard (see Stevenson et al .…”
Section: Methodsmentioning
confidence: 99%
“…Through IWC-SORP, the Acoustic Trends Project working group has built upon the pioneering work done in the first decade of the twenty-first century, and has fostered an increasing number of passive acoustic studies focusing on the calls of Antarctic blue whales and to a lesser extent fin whales across broad time and spatial scales, as well as acoustic data processing and analysis methodology. The data from these studies have been collected both from ships during Antarctic voyages and from long-term moored recording devices 4, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . The project working group presently (as of March 2020) has access to more than 300,000 h of passive acoustic data that have been collected throughout the Southern Ocean over the past 20 years.…”
mentioning
confidence: 99%
“…Erbs et al, 2017; Keating et al, 2015) and vocalisations of baleen whales (e.g. Miller et al, 2016). Gillespie et al (2013) reported a recall of 88% (the percentage of manual detections which were detected automatically).…”
Section: Discussionmentioning
confidence: 99%